2021
DOI: 10.20870/ijvr.2021.21.2.4620
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on Extended Reality: Virtual, Augmented and Mixed Reality in Working Life

Abstract: Extended reality (XR), here jointly referring to virtual, augmented, and mixed (VR, AR, MR) reality, is becoming more common in everyday working life. This paper presents a systematic literature review of academic publications on XR indicating changes in practical organization of work. We analyse both application areas of XR and theoretical and methodological approaches of XR research. The review process followed the PRISMA statement. Design, remote collaboration, and training were the main application areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…XRU and XREU have a significant impact on the medical experts' use of XRSG for surgery. Ghaednia et al [23] reiterated that the use of SG by surgeons in the application of spinal surgery can be effective in helping the surgeon to perform the procedure better and Vasarainen et al [25] used SG in urological surgery. Zeng et al [13] confirmed in their study that XR technology can help medical experts quickly and accurately locate patients' blood vessels and nerves and found that the usefulness and ease of use of XRSG had a significant positive impact on medical experts' behavior in using XRSG.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…XRU and XREU have a significant impact on the medical experts' use of XRSG for surgery. Ghaednia et al [23] reiterated that the use of SG by surgeons in the application of spinal surgery can be effective in helping the surgeon to perform the procedure better and Vasarainen et al [25] used SG in urological surgery. Zeng et al [13] confirmed in their study that XR technology can help medical experts quickly and accurately locate patients' blood vessels and nerves and found that the usefulness and ease of use of XRSG had a significant positive impact on medical experts' behavior in using XRSG.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Specifically, AR can display computer generated content (e.g., user interfaces and images) on real world scenes in real time [31], while MR can render virtual scenes, combine virtual scenes with real ones, or provide more complex interactivity, i.e., MR achieves a dynamic coexistence of virtual and real content in the same space. Furthermore, some researchers recently proposed extended reality (XR) to encompass AR, MR, and VR [32,33]. Nevertheless, as XR is only an umbrella concept without distinct features, it is not analyzed in this paper.…”
Section: Immersive Technologymentioning
confidence: 99%
“…Extended Reality (XR) itself refers to the amazing use of technology that expands reality and combines the real and virtual worlds. In other words, XR means an umbrella term that combines Virtual Reality (VR), Augmented Reality (AR) and Mixed Reality (MR) (Vasarainen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%